The Effect of Financial Characteristics on Audit Report Lag with Leverage as Moderation - Bagas Prasetyo Jati; Ifah Rofiqoh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research attempts to test firm size, liquidity, profitability against audit report lag with leverage as moderating variable. There is time lag of audit report, whichis a periodic time lag between the end of a fiscal year and the date on which a report on audited finances is issued, that is closely related to the relevance of financialinformation forstakeholders. This study uses secondary data in a quantitative manner from financial statements of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2019–2023. The analytical technique used was of panel data regression using a fixed effect model and moderation analysis. According to the results, both liquidity and profitability show a significant negative impact on the delay in the audit report, while firm size does not have a significant impact. In addition, leverage is shown to moderate the relationship of liquidity with audit report lag; however, no moderation effect found with firm size or profitability on audit report lag. Such findings reflect considerations of company management and auditors that have implications for the timeliness of financial reporting and improving the transparency and credibility of financial information.